International trends in standardizing archival terminology : the Multilingual Archival Terminology (MAT) as a model. Issue 2 (March 2019) - Mohamed, Amany
Abstract : Any discipline, including archival science, has its own terms that form the jargon employed by its specialists. As long as specialists agree amongst themselves on the terms and their definitions, this may facilitate communication and feedback. Arab archives in general, and specialists in particular, will not have an influential international role unless priority is given to standardizing terminology as an important vehicle for international cooperation. The twentieth century witnessed a marked development in international projects aiming at standardizing archival terminology. This development sparked the interest of Arab archivists in the 1980s but efforts to standardize the terminology were by a few individuals rather than by archival institutions. As elsewhere, standardizing Arab archival terminology prevents discrepancies that may arise among specialists. It is thus imperative that archivists and archival establishments coordinate their efforts. This research article investigates trends in standardizing archival terminology by exploring relevant Arab and international projects particularly the ICA's Multilingual Database of Archival Terminology (MAT) as it seeks to incorporate Arabic among its languages in an attempt to engage in the international archival community. The study also sheds light on the problems of finding the exact Arabic equivalents of English and French terminologies.